GAMBARAN PENGGUNAAN OBAT DAN BIAYA PENGOBATAN PENYAKIT TBC PARU PASIEN BPJS RAWAT INAP DI RSUD DOKTER SOEDARSO BULAN SEPTEMBER – NOVEMBER TAHUN 2018 - Dani Suryaningrat; Emma Fitrasari (Jurnal Komunitas Farmasi Nasional, 2021)
Pulmonary TB treatment is a government program that is quite complex because of the long treatment time associated with the required costs. Not a few governments spend medical expenses for TB patients, especially BPJS patients. This study was conducted to determine the cost of treatment for pulmonary tuberculosis in BPJS patients who are hospitalized at RSUD Doctor Soedarso. The research was conducted through a documentation study through a descriptive approach. Data were collected retrospectively from inpatient TB patient data at RSUD Dokter Soedarso. The results showed that the drugs used by TB patients were rifampin, INH 300 mg tab, ethambutol 500 mg tab, Pyrazinamide 500 mg tab, streptomycin inj. Supporting drugs consist of antibiotics, antiemetics, entiulkus, analgesics, mucolytics, supplements, antihistamines, mucolytics, corticosteroids, antifibrinolytics. The cost of TB treatment for pulmonary TB patients with BPJS inpatients on average per patient is TB drugs of Rp. 50,156 (0.55%), supporting drugs 613,141 (16.77), BHP and medical equipment amounting to 211,527 (5.78), Emergency Room at 122,895 (3.36 %), Hospitalization by 1,444,692 (39.53), Doctor's Viste amounting to 364,917 (9.98 %), Lab of 573,511 (15.69%), and Radiology of 273,712 (7.48%). The total cost of treatment per pulmonary TB patient is 3,654,551.